Entecavir Therapy Combined with DNA Vaccination for Persistent Duck Hepatitis B Virus Infection - Foster, Wendy K. (American Society for Microbiology, 2003)
This study was designed to test the efficacy of antiviral treatment with entecavir (ETV) in combination with DNA vaccines expressing duck hepatitis B virus (DHBV) antigens as a therapy for persistent DHBV infection in ducks. Ducks were inoculated with 10(9) DHBV genomes at 7 days of age, leading to widespread infection of the liver and viremia within 7 days, and were then treated orally with either ETV (0.1 mg/kg of body weight/day) or distilled water from 21 days posthatch for 244 days. Treatment with ETV caused a 4-log drop in serum DHBV DNA levels within 80 days and a slower 2- to 3-log drop in serum DHBV surface antigen (DHBsAg) levels within 120 days. Following withdrawal of ETV, levels of serum DHBV DNA and DHBsAg rebounded to match those in the water-treated animals within 40 days. Sequential liver biopsy samples collected throughout the study showed that ETV treatment reduced DHBV DNA replicative intermediates 70-fold in the liver, while the level of the stable, template form, covalently closed circular DNA decreased only 4-fold. ETV treatment reduced both the intensity of antigen staining and the percentage of antigen-positive hepatocytes in the liver, but the intensity of antigen staining in bile duct cells appeared not to be effected. Intramuscular administration of five doses of a DNA vaccine expressing the DHBV presurface, surface, precore, and core antigens, both alone and concurrently with ETV treatment, on days 50, 64, 78, 127, and 141 did not result in any significant effect on viral markers.